Causality, probability, and time - Kleinberg, Samantha (Cambridge University Press, 2013)
"This book presents a new approach to causal inference and explanation, addressing both the timing and complexity of relationships. The method's feasibility and success is demonstrated through theoretical and experimental case studies"--